Non-criteria antiphospholipid antibodies in antiphospholipid syndrome: Diagnostic value added - Liu, Xiangjun; Zhu, Lei; Liu, Hongjiang; Cai, Qingmeng; Yun, Zelin; Sun, Feng; Jia, Yuan; Guo, Jianping; Li, Chun (Frontiers in Immunology, 2022)
Objective: Non-criteria antiphospholipid antibodies (aPLs) increase the diagnostic value for antiphospholipid syndrome (APS) and contribute to better recognition of seronegative APS (SNAPS). However, the clinical utility and the diagnostic value of non-criteria aPLs are inconsistent. The aim of this study was to investigate the prevalence and clinical significance of 7 non-criteria aPLs in a large APS cohort. Methods: Seven non-criteria aPLs, including anti-phosphatidylserine/prothrombin (aPS/PT) antibodies IgG/IgA/IgM, anti-phosphatidylethanolamine antibodies (aPE) IgG/IgA/IgM, anti-Annexin V antibodies (aAnnexinV) IgG/IgA/IgM , anti-phosphatidylserine antibodies (aPS) IgM, aPS IgG , antibodies directed against a mixture of phospholipids (APhL) IgG, and APhL IgM were tested by using the ELISA kits in 175 patients with APS, 122 patients with other autoimmune diseases as disease controls, and 50 healthy controls. Results: In the present study, the highest prevalence of non-criteria aPLs was seen in aAnnexinV (58.86%). APhL IgG and aPS IgM showed the highest specificity (95.35%) and aPS/PT showed the highest Youden index (0.3991) for diagnostic value of APS. The aAnnexinⅤ also showed the highest prevalence in SNAPS (43.3%), followed by APhL IgM (21.7%), aPE (16.7%) and aPS/PT (16.7%). APhL IgG, aPS/PT, and aPS IgG showed positive association with thrombotic events in APS patients [APhL IgG: odds ratio (OR) =2.26, 95% confidence interval (CI) 1.18-4.34, p = 0.013; aPS/PT: OR =2.48, 95% CI: 1.32-4.69, p = 0.004; aPS IgG : OR=1.90, 95% CI 1.01-3.60, p = 0.046; respectively). Inclusion of the non-criteria aPLs increased the accuracy of APS diagnosis from 65.7% to 87.4%. Conclusion: Our data provide evidence that addition of the non-criteria aPLs can improve the diagnostic accuracy in APS. APhL IgG, aPS/PT, and aPS IgG may be potential biomarkers to predict the risk of thrombosis in APS.